Comparison between Stromal Vascular Fraction and Adipose Mesenchymal Stem Cells in Remodeling Hypertrophic Scars. - Sophie Domergue; Claire Bony; Marie Maumus; Karine Toupet; Eric Frouin; Valérie Rigau; Marie-Catherine Vozenin; Guy Magalon; Christian Jorgensen; Danièle Noël (PLoS ONE)
Hypertrophic scars (HTS) are characterized by excessive amount of collagen deposition and principally occur following burn injuries or surgeries. In absence of effective treatments, the use of mesenchymal stem/stromal cells, which have been shown to attenuate fibrosis in various applications, seems of interest. The objectives of the present study were therefore to evaluate the effect of human adipose tissue-derived mesenchymal stem cells (hASC) on a pre-existing HTS in a humanized skin graft model in Nude mice and to compare the efficacy of hASCs versus stromal vascular fraction (SVF). We found that injection of SVF or hASCs resulted in an attenuation of HTS as noticed after clinical evaluation of skin thickness, which was associated with lower total collagen contents in the skins of treated mice and a reduced dermis thickness after histological analysis. Although both SVF and hASCs were able to significantly reduce the clinical and histological parameters of HTS, hASCs appeared to be more efficient than SVF. The therapeutic effect of hASCs was attributed to higher expression of TGFβ3 and HGF, which are important anti-fibrotic mediators, and to higher levels of MMP-2 and MMP-2/TIMP-2 ratio, which reflect the remodelling activity responsible for fibrosis resorption. These results demonstrated the therapeutic potential of hASCs for clinical applications of hypertrophic scarring.